Periodic and aperiodic variability of the interacting binary and long-periodic stars - Andronov, I. L.; Baklanov, A. V.; Chinarova, L. L.; Chochol, D.; Gazeas, K.; Halevin, A. V.; Kolesnikov, S. V.; Kudashkina, L. S.; Marsakova, V. I.; Mason, P. A.; Niarchos, P. G.; Patkos, L.; et al. (2000)
Recent results obtained within the framework of the international observational and research campaigns are reviewed. The main topics are following: magnetic cataclysmic variables: synchronization of the spin and orbital period of the white dwarf; observational evidence on the switching of the accretion from one pole to another; non-dipole configuration of the magnetic field; ``swingings'' of the orientation of the magnetic axis in the `` synchronous systems''; instability of the accretion and the ``red noise''; long-term luminosity changes; UV Cet - like flares; two-pole accretion in the intermediate polars; weakly- and non- magnetic cataclysmic variables: negative and positive superhumps in the nova-like variables; ``red noise'' and/or quasi-periodic oscillations; unprecedented switch of the superhump period in TT Ari; the luminosity dependence of the superhump period in BZ Cam and V725 Aql; long-term variations of the outburst characteristics of dwarf novae and luminosity of old novae - magnetic activity of the red secondary vs third body orbiting around a cataclysmic variable; symbiotic binaries: light curve variations in symbiotic novae and stars with a pulsating component; long-periodic pulsating variables: statistical study of the characteristics of the mean phase curves and of the individual cycles; additional classification criteria for the Mira-type and semi-regular stars. Some of the original papers are available at http://www.paco.odessa.ua/~il-a and http://ila.webjump.com